Smart Home: Controlling and Monitoring Households Appliances using GSM Network - Budi Rahmadya; Fahrul Ghazi; Derisma Derisma (Computer Engineering and Applications Journal, 2016)
This study discussed about using the smart home automation systems for household appliances such as lights and fans, by utilizing the GSM network as a communication medium to control and monitor the household appliances. In this study, the simulations were performed by the two following modes 1). Self-automated and 2). Manually-automated. In controlling the lamp, the light intensity that values less than 280 lux will give response of turned ON the lamp, while if the value of light intensity is more than 280 lux, it will give a response of turned OFF the lamp. To control the fan, a room temperature value of more than or equal to 30 ° C will turn ON the fan, while the room temperature value which is less than 30 ° C will turn OFF the fan. Simulations were performed by placing the devices in the room and operating it for three days. The test and simulation results were recorded in the form of log files or history files. The self-automated operations mode controlled the system using a sensor (Light Dependent Resistor and LM35 Sensor) unit to detect the environmental condition and take actions according to detected environmental condition. In the manually-automated operation mode, user could control the household appliances according to the user’s intention. The light intensity values obtained in the morning were equal to 280 lux, so it will turn off the lights. The room temperature obtained was in the range of 28oC - 33oC; the fan will turn on if the temperature value is equal to or more than 30oC.